Phosphodiesterase 5 Inhibitors from Derris scandens - Chaichamnong, Nattiya; Temkitthawon, Prapapan; Khorana, Nantaka; Pitpakdeeanan, Prompan; Taepavarapruk, Pornnarin; Nuengchamnong, Nitra; Siriwattanasathien, Yuthana; Suksamrarn, Apichart; Ingkaninan, Kornkanok (Planta Medica, 2018)
Phosphodiesterase 5 inhibitors have been used as a first-line medicine for the treatment of erectile dysfunction. In the search for new phosphodiesterase 5 inhibitors from natural sources, we found that the 95% ethanol extract of Derris scandens stem showed phosphodiesterase 5 inhibitory activity with an IC50 value of about 7 µg/mL. Seven isoflavones and a coumarin constituent isolated from this plant were investigated for phosphodiesterase 5 inhibitory activity. The results showed that osajin (8), 4′,5,7-trihydroxybiprenylisoflavone (4), and derrisisoflavone A (2) had the ability to inhibit phosphodiesterase 5 with IC50 values of 4, 8, and 9 µM, respectively. These compounds exhibited selectivity on phosphodiesterase 5 over phosphodiesterase 1, however, the selectivity on phosphodiesterase 5 over phosphodiesterase 6 was low. In order to quantitatively determine these bioactive constituents in D. scandens extract, LC-QTOF-MS method has been developed and validated. The limit of quantitation values in the range of 0.1 – 5 µg/mL were obtained. The assay showed satisfactory precision and accuracy. The results from our method showed that the 95% ethanol extract of D. scandens stem was comprised of all eight compounds, with derrisisoflavone A (2) and lupalbigenin (3) presenting as the major constituents.
Keywords: Derris scandens; Fabaceae; phosphodiesterase 5; erectile dysfunction; isoflavoner; LC-QTOF-MS